NF1 regulates mesenchymal glioblastoma plasticity and aggressiveness through the AP-1 transcription factor FOSL1 - Marques, Carolina; Unterkircher, Thomas; Kroon, Paula; Oldrini, Barbara; Izzo, Annalisa; Dramaretska, Yuliia; Ferrarese, Roberto; Kling, Eva; Schnell, Oliver; Nelander, Sven; Wagner, Erwin F; Bakiri, Latifa; et al. (eLife, 2021)
The molecular basis underlying glioblastoma (GBM) heterogeneity and plasticity is not fully understood. Using transcriptomic data of human patient-derived brain tumor stem cell lines (BTSCs), classified based on GBM-intrinsic signatures, we identify the AP-1 transcription factor FOSL1 as a key regulator of the mesenchymal (MES) subtype. We provide a mechanistic basis to the role of the neurofibromatosis type 1 gene (NF1), a negative regulator of the RAS/MAPK pathway, in GBM mesenchymal transformation through the modulation of FOSL1 expression. Depletion of FOSL1 in NF1-mutant human BTSCs and Kras-mutant mouse neural stem cells results in loss of the mesenchymal gene signature and reduction in stem cell properties and in vivo tumorigenic potential. Our data demonstrate that FOSL1 controls GBM plasticity and aggressiveness in response to NF1 alterations.
Keywords: GBM; mesenchymal; NF1; FOSL1; FRA-1